The prince of this world - Kotsko, Adam (Stanford, California : Stanford University Press, 2016)
The most enduring challenge to traditional monotheism is the problem of evil, which attempts to reconcile three incompatible propositions: God is all-good, God is all-powerful, and evil happens. The Prince of This World traces the story of one of the most influential attempts to square this circle: the offloading of responsibility for evil onto one of God's rebellious creatures. In this striking reexamination, the devil's story is bitterly ironic, full of tragic reversals. He emerges as a theological symbol who helps oppressed communities cope with the trauma of unjust persecution, torture, and death at the hands of political authorities and eventually becomes a vehicle to justify oppression at the hands of Christian rulers. And he evolves alongside the biblical God, who at first presents himself as the liberator of the oppressed but ends up a cruel ruler who delights in the infliction of suffering on his friends and enemies alike. In other words, this is the story of how God becomes the devil-a devil who remains with us in our ostensibly secular age.
Introduction : why the devil? -- The Hebrew biblical tradition : the paradox of minority monotheism -- The New Testament and early Christianity : apocalyptic and its Christian vicissitudes -- Monasticism and medieval Christianity : the ransom paid the devil -- The fall of the devil -- The earthly city -- Life in hell -- Conclusion : the legacy of the devil.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Devil -- Christianity -- History of doctrines; Good and evil -- Religious aspects -- Christianity; RELIGION -- Christian Theology -- Angelology & Demonology; Good and evil -- Religious aspects -- Christianity